Pengaruh Struktur Modal dan Tata Kelola Perusahaan terhadap Nilai Perusahaan pada Perusahaan Perbankan BUKU 4 - Sulistiana, Leza; Siska, Elmira (Lembaga Pengembangan Kinerja Dosen, 2024)
A balanced DER can increase company value. Appropriate managerial ownership can increase company value. This research aims to analyze the influence of capital structure with the DER proxy and corporate governance with the managerial ownership proxy both partially and simultaneously on firm value with the MVE proxy in BUKU 4 banking companies that IPO on the IDX for the 2019-2023 period. In this research, quantitative research methods were used. The population used was companies participating in the banking group that conducted an IPO on the IDX from 2019 to 2023. The sampling method used a purposive sampling method so that 6 banks were selected. The research data was processed using the classic Asumi test, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination test. The results of this study show that the data does not have econometric problems. Partially, DER has a positive and significant effect on MVE as evidenced by t count > t table and significant values ​​< 0.05 or 5,038 > 1,701 and 0.000 < 0.05. Partially, managerial ownership has a positive and significant effect on MVE as evidenced by t count > t table and significant values ​​< 0.05 or 3,105 > 1,701 and 0.004 < 0.05. Simultaneously DER and managerial ownership have a positive and significant effect on MVE as evidenced by calculated f > f table 21,356 > 4,200 and a significant value of 0.000 < 0.005.